Effect of the combination of Benson's relaxation technique and brief psychoeducational intervention on multidimensional pain and negative psychological symptoms of pregnant women: A randomized controlled trial - Mohammad Mehdi Mohammadi; Shima Parandin (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Pregnancy is associated with negative psychological symptoms (NPS) and multidimensional pain. Therefore, the present study was conducted to determine the effect of the combination of Benson's relaxation technique (BRT) and brief psychoeducational intervention (BPI) on multidimensional pain and NPS of pregnant women. MATERIALS AND METHODS: The present randomized clinical trial was conducted on pregnant women referred to Imam Reza and Motazedi Hospitals in Kermanshah, Iran. In this regard, 60 pregnant women were randomly allocated to intervention (n = 30) and control (n = 30) groups. The groups attended BRT and BPI educational sessions for 4 weeks, but the control group received no intervention. Subsequently, both groups completed Depression Anxiety Stress Scale-21 and multidimensional pain inventory. RESULTS: The mean NPS (stress, anxiety, and depression) was significantly decreased in the intervention group (P < 0.001), while no statistically significant differences were observed in the control group (P > 0.05). The independent t-test revealed a significant difference between the mean scores of intervention and control groups (P < 0.001). The mean multidimensional pain was significantly decreased in mothers after the completion of educational sessions (P < 0.001), and the independent t-test results indicated a significant difference between the scores of the intervention and control groups (P < 0.001). CONCLUSION: The results of this study suggested that the combination of BRT and BPI can lead to a reduction in the NPS and multidimensional pain in the pregnant women. This intervention is recommended to be considered as part of a healthcare program in pregnant mothers.